Methyl(2-mercapto-4-methylpyrimidinato)mercury(II): A methylmercury(II) derivative with an unusual metal-metal interaction - Bravo, Jorge; Casas, José S.; Mascarenhas, Yvonne P.; Sánchez, Agustín; Santos, Carlos de O. P. [UNESP]; Sordo, José (Royal Society of Chemistry (RSC), 1986)
4-Methylpyrimidine-2-thione reacts with methylmercury hydroxide to give the thiolate derivative HgMe(SC4H2N2Me-2), the X-ray structure of which reveals pairs of molecules with a mercury-mercury distance of 3.10 Å.